Avaliação da densidade média da madeira do povoamento de Eucalyptus spp de empresas do setor madereiro do estado de São Paulo - Bruder, Edson Marcelo; Katz, Ieoschua; Rezende, Marcos Antonio de [UNESP] (My University, 2010)
The Brazil has the largest tropical forest of planet. The forestry in State of São Paulo is prevalent in plantation of genus Eucalyptus spp. used for a variable finalities. This species is more planted in short-cicle forest in Brazil and the world. The increase of wood consumption in the last decade, due to industrial demand in the forest sector in development and due for expansive international demand forest products. The density have an expressive evidence how one of the major indices to evaluate the wood quality for companies. The optimization of techniques to determinate the density is very important. The objective of this study was identify the representive tree average size and density in technical optimization to determine the density for sample analysis acquisition. This study used six trees of the genus Eucalyptus spp. the samples was cut in disc form the every one meter, until the commercial height (hc). The density of samples was determinate by direct method to 0% of the humidity. The software Origin Professional Version 7.0 used for adjustment of equations of density variations. The results showed that the Ideal of Sampling Position (PIA) was determined in 0,46hc position. The study concluded the viability of significant number reduction from samples trees and the acquisition of a single disc between 40 and 50 of commercial height. The productivity demonstrated evidence of a reliable index of investment and cost less than 1% of the net.

Brasil posee la mayor floresta tropical del planeta. El género Eucalyptus spp se destaca entre las especies más plantadas en Brasil y en el mundo. Hubo un aumento de la utilización de madera en las últimas décadas debido a la demanda de las industrias en el sector forestal en desenvolvimiento. El objetivo es identificar la altura representativa de la densidad media y optimizar la técnica de obtención de la densidad media del árbol por las empresas del sector maderero. Fueron utilizados seis árboles del género Eucalyptus spp. recortados de metro en metro hasta la altura comercial (hc). Por medio de ecuaciones se determinó la densidad a 0% de humedad y la básica. Se determinó un índice de inversión para la mejora en los resultados por medio de demostraciones financieras. El software Origin Professional Version 7.0 fue utilizado para ajuste de las ecuaciones del tipo polinomial de las variaciones de la densidad y a la identificación del punto de máxima y mínima densidad. La posición ideal de muestreo (PIA) fue encontrado en la posición de 0,46hc. El histórico de la productividad se convirtió en un buen índice para tornar la empresa eficiente. El estudio posibilitó la viabilidad de reducción del número de muestras y demostró viabilidad de retirada de un único disto entre 40 e 50% da altura comercial y la productividad presentó evidencia de un índice confiable de inversión y el coste inferior al 1% de la red.

O Brasil possui a maior floresta tropical do planeta. O gênero Eucalyptus spp destaca-se dentre as espécies mais plantadas no Brasil e no mundo. Houve um aumento da utilização de madeira nas últimas décadas devido à demanda das indústrias no setor florestal em desenvolvimento. O objetivo é identificar a altura representativa da densidade média e otimizar a técnica de obtenção da densidade média da árvore pelas empresas do setor madeireiro. Foram utilizadas seis árvores do gênero Eucalyptus spp. recortadas de um em um metro até a altura comercial (hc). Por meio de equações determinou-se a densidade a 0% de umidade e a densidade básica. Determinou-se um índice de investimento para a melhora nos resultados por meio das demonstrações financeiras. O software Origin Professional Version 7.0 foi utilizado para ajuste das equações do tipo polinomial das variações da densidade e a identificação do ponto de máxima e mínima densidade. A posição ideal de amostragem (PIA) foi encontrado na posição de 0,46hc. O histórico da produtividade tornou-se um bom índice para tornar a empresa eficiente. O estudo possibilitou a viabilidade de redução do número de amostras e demonstrou viabilidade de retirada de um único disco entre 40 e 50% da altura comercial e a produtividade apresentou evidências de um índice confiável de investimento e custo inferior a 1% do lucro líquido.
Evaluation of medium density of short-cicle tree, genus Eucalyptus spp, of lumber sector in São Paulo State
Evaluación de la densidad media de la madera de la población de Eucalyptus spp. de empresas del sector madeirero del estado de São Paulo
Keywords: Basic density; Density; Eucalyptus; Forest sector; Management cost; Densidad; Densidad básica; Eucalyptus; Gestión de costos; Sector maderero; Densidade; Densidade básica; Eucalyptus; Gestão de custos; Setor madeireiro